Backpacks and school children's obesity: challenges for public health and ergonomics - De Paula, A. J. F. [UNESP]; Silva, J. C. P.; Paschoarelli, Luis Carlos [UNESP]; Fujii, J. B. (IOS Press, 2012)
This descriptive study of cross sectional has focused on analyzing the school material weight transported by students associated with children and adolescents overweight in primary and secondary schools. Participants 339 students of both genders, aged 10-19 years. 243 students carrying and average load of 12.65% of his body weight. 53 students were overweight with a BMI of 20,00 to 35,6. 20 overweight students carrying backpacks more than 10% of his body weight. 21% of the students rated complained of back and shoulder pain. This data is very important in the preventive aspects for the individuals studied, as well as others with the same anthropometric characteristics and the same demand.
Keywords: school backpack; ergonomics; BMI; back pain; posture